1989
DOI: 10.1111/j.1365-3059.1989.tb01424.x
|View full text |Cite
|
Sign up to set email alerts
|

Fungicide and nitrogen applications in relation to the improvement of disease control and yield in winter barley

Abstract: In crops of winter barley, cvs Igri and Halcyon, crop structure and intensity of foliar diseases were altered by delaying the main top dressing of nitrogen until mid‐April. A single application of fungicide then was sufficient to decrease substantially the severity of fungal disease and improve grain yield at harvest. Disease control and yield responses were greatest when fungicides were applied during a 3‐week period after the main nitrogen application in April. No additional yield benefits were obtained by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…At higher N, fungal diseases could be an important limiting factor on yield increase, so more fungicides should perhaps be applied to reduce the risk of yield losses. This result is similar to the results obtained by Jordan et al (1989). In addition, the timing of nitrogen dressings had a significant effect on the progress of stem base and foliar diseases ( Clare et al 1990).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…At higher N, fungal diseases could be an important limiting factor on yield increase, so more fungicides should perhaps be applied to reduce the risk of yield losses. This result is similar to the results obtained by Jordan et al (1989). In addition, the timing of nitrogen dressings had a significant effect on the progress of stem base and foliar diseases ( Clare et al 1990).…”
Section: Discussionsupporting
confidence: 86%
“…Disease control and the yield response of barley were greatest when fungicides were applied during a 3‐week period after the main nitrogen application in April. No additional yield benefits were obtained by carrying out two fungicide applications ( Jordan et al 1989). Hanus and Schoop (1987) showed that the application of fungicides also increased the wheat and barley yield potential, but the yield variability over the treatments remained the same, except for the high N application rate of >200 kg ha −1 .…”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence that the timing of N applications can also influence disease development (Jordan et al , 1989; Olesen et al , 2003 b ). Early applications of the main spring dose to winter barley resulted in a greater severity of foliar disease compared with delayed applications (Jordan et al 1989).…”
Section: Nutrition and Plant Disease: Implications For Controlling Plmentioning
confidence: 99%
“…There is some evidence that the timing of N applications can also influence disease development (Jordan et al , 1989; Olesen et al , 2003 b ). Early applications of the main spring dose to winter barley resulted in a greater severity of foliar disease compared with delayed applications (Jordan et al 1989). Similarly, early applications to winter wheat increased the severity of yellow rust (Neumann et al , 2004), powdery mildew and Septoria (Olesen et al , 2003 a ) compared with later applications.…”
Section: Nutrition and Plant Disease: Implications For Controlling Plmentioning
confidence: 99%
“…Two-spray programmes commonly give larger responses than a single spraying (Jordan & Stinchcombe 1986;Cunningham & Dunne 1991). Leaf diseases and responses to fungicide sprays can also be modified by the timing of nitrogen applications (Jordan et al 1985;Jordan & Stinchcombe 1986;Jordan et al 1989) and it has been suggested that if the timing of nitrogen applications in spring is optimal, only a single fungicide spray is necessary to obtain economic control of leaf diseases in winter barley. Thus in an experiment in 1987 on winter barley (cv.…”
Section: Introductionmentioning
confidence: 99%